Dinâmica populacional do cágado-de-barbicha (Phrynops geoffroanus; Chelidae) em área urbana - LARISSA LOPES SEINO (2021)
Abundance and survival are parameters that bring important information about demographic aspects and allow, for example, to estimate the variations and the viability of a population in the long term. Biotic and abiotic factors can influence the survival of a population, such as sex, age and the seasonality of the environment. Apparent survival is a concept that estimates the proportion of individuals without distinguishing between mortality and emigration. The objective of the work was to verify if sex, weight and / or seasonality affect the apparent survival of Phrynops geoffroanus (Chelidae) and to estimate the abundance of the population in an urban area. A mark-recapture data was collected using hoop traps along 185 meters of river in two seasons (dry and rainy) from 2015 to 2020. The robust model of “Huggins Full Heterogeneity” was used to estimate the capturability, the survival apparent and population abundance. 131 individuals were captured (54 females and 77 males). Apparent survival was lower for males, mainly in the transition from the rainy season to the dry season. The effect of weight, a proxy for age, showed stability and high apparent survival for smaller individuals (young) and differed between sexes with males decreasing their apparent survival when older. The population's abundance oscillated around 38 individuals, with no evidence of sex bias. Given the high longevity of the species (around 70 years), we can deduce that individuals, for the most part, leave the population through emigration. Thus, the difference in the survival of males and females may be due to the different dispersive behaviors during the reproductive period, since females seek an environment for nesting, while males are distributed in search of sexual partners. The greater dispersion of males during the rainy season coincides with the mating period of the species, in addition to the greater availability of wetlands. The high survival of juveniles can be evidence that the environment is favorable for the species, having the necessary resources for the residence of the females and juveniles.